Analisis Moderasi Cash Position Terhadap Profitabilitas dan Likuiditas pada Kebijakan Dividen - Jerico Dennis; Rini Tri Hastuti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine and analyze the role of cash position as a moderating variable in the relationship between profitability and liquidity on dividend policy in banking sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. Profitability is proxied by Return on Equity (ROE), liquidity by Current Ratio (CR), cash position by Cash Position (CP), and dividend policy by Dividend Payout Ratio (DPR). This research employs a descriptive-causal quantitative approach using purposive sampling, resulting in a final sample of 8 banking companies with 40 observations. The findings reveal that profitability has a positive and significant effect on dividend policy, while liquidity does not have a significant effect. Furthermore, cash position is not proven to moderate the influence of either profitability or liquidity on dividend policy. These results indicate that dividend decisions in the banking sector are primarily profit-driven, with cash position serving merely as a technical payment instrument rather than a strategic determinant of dividend policy.